Electromechanical Performance Analysis of the Hybrid Piezoelectric-Electromagnetic Energy Harvester under Rotary Magnetic Plucking Excitation - Hongyan Wang; Jiarui Hu; Gang Sun; Liying Zou (Shock and Vibration)
This paper presents an analysis of the hybrid piezoelectric-electromagnetic energy harvester (P-EMEH) driven by contactless rotary magnetic plucking. A lumped-parameter model of the hybrid P-EMEH is developed, and the model parameters are determined from the finite element analysis (FEA) method. A parametric study is conducted to investigate the effects of driving force parameters, load resistance, and electromechanical coupling strengths (EMCSs) on the maximal displacements and velocities, average power inputs and outputs, and energy efficiencies of the system for indicating the performance of the hybrid P-EMEH. The results show that the hybrid P-EMEH can obtain the improved power inputs by reducing the gyration radii of the rotary magnet and shortening the gaps between the two magnets. The structural vibrations can be strongly suppressed owing to the optimal piezoelectric power outputs, which can lead to the occurrence of valleys’ power of the electromagnetic element. At weak coupling, the hybrid P-EMEH can achieve higher power outputs than the single piezoelectric energy harvester (PEH) and the single electromagnetic energy harvester (EMEH). At strong coupling, the use of the PEH is more advantageous for energy harvesting due to wider power bandwidths at high dimensionless frequencies when compared with the hybrid P-EMEH. This work provides a fundamental understanding on the effect of load resistance and EMCSs on the dynamic and electrical characteristics of the magnetically plucked hybrid P-EMEH.